Understanding daily problematic social media use of young adults: the role of trait- and state-fear of missing out. - Gao, Xuemei; Li, Jiayu; Bai, Xujia; Zhou, Yuhong; Jiang, Xintong (Psychology & Health, 2026)
Fear of missing out (FoMO) is strongly associated with problematic social media use (PSMU) in young adults; however, little is known about the different roles of trait-FoMO and state-FoMO in PSMU. This longitudinal study used 9-consecutive-day ecological momentary assessment (EMA) to investigate the momentary association between state-FoMO and PSMU and to determine whether such association is moderated by trait-FoMO. We used EMA to measure three daily social media use variables (i.e. craving, time spent on social media, and daily social media self-control failure) to determine daily PSMU. 129 female undergraduates (Mage = 20.48, SD = 1.47) completed a total of 4290 EMA surveys. All main variables were significantly and positively correlated with each other at baseline. Multilevel models revealed that the association of momentary state-FoMO with PSMU was significantly positive. Furthermore, trait-FoMO only moderated the positive association between daily state-FoMO and craving. Specifically, trait-FoMO enhanced the influence of daily state-FoMO on craving, and individuals with lower state-FoMO were more susceptible to the effects of trait-FoMO than individuals with higher state-FoMO. Different implications of trait-FoMO and state-FoMO are discussed particularly regarding their potential to increase the risk of young adult PSMU.